1985
DOI: 10.1254/jjp.37.39
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the Binding of O-Ethyl O-p-Nitrophenyl 3henylphosphonate (EPNoxon) to Microsomal Carboxylesterase by NAD in vitro

Abstract: Abstract-Inhibition of rat liver microsomal carboxylesterase(CEase) by 0-ethyl 0-p nitrophenyl phenylphosphonothioate (EPN) and binding of EPN oxygen analog to microsomal CEase were enhanced by addition of NAD or NADP. This was more prominent in addition of NAD than NADP. No potentiation of anti-CEase action of EPN by NAD was seen when pure esterase (E.C. 3.1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…Namely, binding of oxygen analogs of these com pounds to CEase, a nonvital enzyme may, reduce the anti -chol1nergic action of organophosphorus insecticides. In conclusion, taken together with our previous papers (1,2) and unpublished observation (S. Sugiyama et al), the present results strongly suggest that an enzymatic conversion of NAD to NADH by microsomal dehydrogenase(s) may be, at least in part, involved in binding of the organophosphate insecticides formed in vivo to CEase, by which, in turn, toxicities of these insecticides are reduced.…”
Section: Methodssupporting
confidence: 88%
See 3 more Smart Citations
“…Namely, binding of oxygen analogs of these com pounds to CEase, a nonvital enzyme may, reduce the anti -chol1nergic action of organophosphorus insecticides. In conclusion, taken together with our previous papers (1,2) and unpublished observation (S. Sugiyama et al), the present results strongly suggest that an enzymatic conversion of NAD to NADH by microsomal dehydrogenase(s) may be, at least in part, involved in binding of the organophosphate insecticides formed in vivo to CEase, by which, in turn, toxicities of these insecticides are reduced.…”
Section: Methodssupporting
confidence: 88%
“…So, involvement of NAD-dependent dehy drogenase (s) in liver microsomes in the NAD-effect was studied. We have already reported that addition of NEM to the incubation mixture containing liver micro somes, EPN and NAD caused a remarkable decrease of the NAD-effect (2) . In this study, degree of formation of EPNoxon from EPN in the incubation mixture was decreased ( Table 2).…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations